The impact of glucocorticoids and statins on sleep quality. (February 2021) - Szmyd, Bartosz; Rogut, Magdalena; Białasiewicz, Piotr; Gabryelska, Agata
Summary: Glucocorticoids and statins are the foundation of lifelong therapies and as such, may generate a variety of side effects. Among these, sleep impairments are one of the least explored and, simultaneously, majorly underestimated in clinical practice. Based on the available evidence, we have concluded that glucocorticoid action on the suprachiasmatic nucleus (SCN) that drives sleep disturbances is dual in nature. It involves both serotonin depletion and reduced arginine vasopressin signalling in the SCN. The former seems to involve activation of glucocorticoid receptors in the dorsal raphe, whereas the latter likely results from changes in glucose serum levels affecting the SCN, among other blood-borne factors which are yet to be discovered. Literature remains inconclusive when it comes to statins. Their diverse potential to cross the blood–brain barrier is considered the key factor determining statins' capability to evoke sleep impairments. Concurrently, an effect similar to that produced by steroids occurs – alteration in serum levels of blood-borne factors, such as glucose, which is a likely cause of statin-induced sleep disturbances.